A systematic review of economic analyses of active transport interventions that include physical activity benefits. (January 2016) - Brown, Vicki; Diomedi, Belen Zapata; Moodie, Marj; Veerman, J. Lennert; Carter, Rob
Abstract: Physical inactivity is one of the leading causes for the growing prevalence of non-communicable diseases worldwide and there is a need for more evidence on the effectiveness and cost-effectiveness of interventions that aim to increase physical activity at the population level. This study aimed to update a systematic review published in 2008 by searching peer-reviewed and unpublished literature of economic evaluations of transport interventions that incorporate the health related effects of physical activity. Our analysis of methods for the inclusion of physical activity related health effects into transport appraisal over time demonstrates that methodological progress has been made. Thirty-six studies were included, reflecting an increasing recognition of the importance of incorporating these health effects into transport appraisal. However, significant methodological challenges in the incorporation of wider health benefits into transport appraisal still exist. The inclusion of physical activity related health effects is currently limited by paucity of evidence on morbidity effects and of more rigorous evidence on the effectiveness of interventions. Significant scope exists for better quality and more transparent reporting. A more consistent approach to the inclusion of benefits and disbenefits would reinforce the synergies between the health, environmental, transport and other sectors. From a transport sector perspective the inclusion of physical activity related health benefits positively impacts cost effectiveness, with the potential to contribute to a more efficient allocation of scarce resources based on a more comprehensive range of merits. From a public health perspective the inclusion of physical activity related health benefits may result in the funding of more interventions that promote active transport, with the potential to improve population levels of physical activity and to reduce prevalence of physical activity related diseases. Highlights: We examine transport economic evaluations incorporating physical activity effects. Lack of intervention effectiveness evidence and inconsistency in methods exist. Limited inclusion of health effects undervalues benefits of transportation policy. Transport policies could be tools for population health.